2019
DOI: 10.1111/hiv.12778
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of impaired renal function in virologically suppressed people living with HIV compared with controls: the Copenhagen Comorbidity in HIV Infection (COCOMO) study*

Abstract: Objectives While renal impairment is reported more frequently in people living with HIV (PLWH) than in the general population, the PLWH samples in previous studies have generally been dominated by those at high renal risk. Methods Caucasian PLWH who were virologically suppressed on antiretroviral treatment and did not have injecting drug use or hepatitis C were recruited from the Copenhagen Comorbidity in HIV Infection (COCOMO) study. Sex‐ and age‐matched controls were recruited 1:4 from the Copenhagen General… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 41 publications
(61 reference statements)
2
10
0
Order By: Relevance
“…A study conducted in Tanzania also showed that female PLWH initiating ART have higher risk of renal dysfunction (eGFR <60 ml/min/1.73m 2 ) (Msango et al, 2011); similar result was observed in PLWHIV in Denmark (Petersen et al, 2019). While female gender was significantly associated with mild renal impairment (RI) in PLWH in France (Déti et al, 2010).…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…A study conducted in Tanzania also showed that female PLWH initiating ART have higher risk of renal dysfunction (eGFR <60 ml/min/1.73m 2 ) (Msango et al, 2011); similar result was observed in PLWHIV in Denmark (Petersen et al, 2019). While female gender was significantly associated with mild renal impairment (RI) in PLWH in France (Déti et al, 2010).…”
Section: Introductionmentioning
confidence: 76%
“…Sex disparity in RI was observed in both PLWH and HIV-negative individuals (Carrero et al, 2018;Déti et al, 2010;Mocroft et al, 2015;Msango et al, 2011;Neugarten et al, 2019;Petersen et al, 2019). Available data in general population not only showed higher risk of CKD in female than in male that observed in PLWH, but also documented more rapid progression of kidney function decline in male than female in HIV-negative people (Carrero et al, 2018;Neugarten et al, 2019).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The Copenhagen Comorbidity in HIV Infection Study [92] has demonstrated that HIV infection is an independent risk factor for renal impairment development, probably because of chronic inflammation and coagulation activation induced by HIV infection. Furthermore, it showed that the risk of renal impairment was higher in older PLWH compared to younger PLWH [100]. In fact, the kidneys act as an HIV reservoir and the resulting polyclonal gammaglobulinemia, immune complex and cryoglobulin production, and glomerular injury are consequences of T-cell-dependent B response hy-peractivation.…”
Section: Chronic Kidney Diseasementioning
confidence: 99%
“…The PLWH's quality of life (QoL), usually defined as an individual's overall perception of their physical state, psychological functions, social ability, and individual comprehensive conditions based on social economy, cultural background, and value orientation [10], is generally lower than that of the general population, due to HIV-related disabilities [6] and ongoing widespread stigma [11][12][13]. The old PLWH, compared to the young PLWH and the general old population, usually face a higher level of stigma [13,14], a high risk of comorbidity [15], more side effects from antiretroviral therapy (ART) [16], and less social support from friends or families [17]. Recent studies have examined the roles of interpersonal and social factors in the QoL among PLWH in China, revealing that social trust and social connection may be associated with a mental health summary (MCS) score of QoL [18].…”
Section: Introductionmentioning
confidence: 99%